From Hard Rock to Hadrah: Music and Youth Sufism in Contemporary Indonesia - M Mukhsin Jamil (Teosofia: Indonesian Journal of Islamic Mysticism, 2020)
Many studies on Islam in Indonesia usually focus on Islamic movements from social, economic, or political perspective. One missing viewpoint that does not get much attention or even completely ignored is the spiritual life of the Muslim youths. This study would examine and analyze the growth of the Syeikhermania and their attachment to Hadrah music of Majelis Shalawat Ahbab al-Musthofa led by Habib Syeikh Abdul Qadir Assegaf, an Arabic-descent Muslim preacher. Unlike Muslim youth organizations that are enthusiastically active in political movements that tend to be radical, Syeikhermania plays a role in creating harmony and tolerance. They transform spiritually from Hard Rock to Hadrah music. Therefore, this study disclosed the participation of the Muslim youths in the Majelis Shalawat Ahbab al-Musthofa which is motivated by the need for spiritual protection and expressing their identity as Muslim youths in contrast to the liberal and secular cultures on the one hand and fundamentalist and radicalist groups on the other hand.